HERBAL TREATMENT FOR SIDE EFFECTS OF ANTI ANXIETY DRUGS - Jainam Shah; Nadim Chhipa; Pragnesh Patani (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
• Anxiety is characterized by feelings of unease, dread, and fear. It could make you sweat, feel fretful and tense, and have a fast heartbeat. It very well may be an ordinary response to strees.• For example, you could feel restless when confronted with troublesome issue at work, prior to stepping through an exam, or prior to pursuing a significant choice. It can assist you with adapting.• uneasiness disorder are condition in which you have nervousness that doesn't disappear and can deteriorate over the long run. The reason for tension is obscure. Component, for example, genetic, brain biology, and chemical science, stress, and your current circumstance might assume a part.the uneasiness issues share self-announced Side effects of tension and dread; uplifted nervousness and dread answering prompts that signal danger, signals that signal no danger, prompts that previously flagged danger, and settings related with danger; raised pressure reactivity to aversive upgrades; attentional predispositions to danger important improvements(1).